Moral Partiality and Duties of Love - Berit Brogaard (Philosophies, 2023)
In this paper, I make a case for the view that we have special relationship duties (also known as “associative duties”) that are not identical to or derived from our non-associative impartial moral obligations. I call this view “moral partialism”. On the version of moral partialism I defend, only loving relationships can normatively ground special relationship duties. I propose that for two capable adults to have a loving relationship, they must have mutual non-trivial desires to promote each other’s interests or flourishing and to respect each other’s core values. Along the way, I critically ascertain three alternative accounts of what normatively grounds special relationship duties and argue that my proposed view avoids the problems plaguing the alternatives.